Impacto do tamanho das instituições de longa permanência na adesão às orientações de prevenção de infecções por COVID-19 - Wachholz, Patrick Alexander [UNESP]; Melo, Ruth Caldeira de; Jacinto, Alessandro Ferrari; Villas Boas, Paulo José Fortes [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to evaluate the adherence of Brazilian long-term care facilities to the World Health Organization Infection Prevention and Control guidance, and assess the association of their size with the adherence to these recommendations. METHOD: cross-sectional study conducted with facilities' managers. Authors developed a 20-item questionnaire based on this guidance, and a global score of adherence, based on the adoption of these recommendations. Adherence was classified as (1) excellent for those who attended ≥14 out of 20 recommendations; (2) good for 10 to 13 items; and (3) low for those with less than ten items. Facilities' sizes were established as small, intermediate, and large according to a two-step cluster analysis. Descriptive statistics and chi-square tests were used at a 5% significance level. RESULTS: among 362 included facilities, 308 (85.1%) adhered to 14 or more recommendations. Regarding its size, adherence to screening COVID-19 symptoms of visitors (p=0.037) and isolating patients until they have had two negative laboratory tests (p=0.032) were lower on larger ones compared to medium and small facilities. CONCLUSION: adherence to COVID-19 mitigation measures in Brazilian facilities was considered excellent for most of the recommendations, regardless of the size of the units.

OBJETIVO: evaluar la adhesión de instituciones brasileñas de larga estancia a las orientaciones de Prevención y Control de Infecciones de la Organización Mundial de la Salud y evaluar la asociación entre su tamaño y la adhesión a esas recomendaciones. MÉTODO: estudio transversal realizado con gerentes de establecimientos. Los autores desarrollaron un cuestionario de 20 ítems basado en estas directrices y un puntaje general de cumplimiento acorde a la observancia de estas recomendaciones. La adhesión se calificó (1) excelente para aquellas que cumplieron con ≥14 de 20 recomendaciones; (2) buena para 10 a 13 artículos; y (3) baja para aquellas con menos de diez elementos. El tamaño de las instalaciones se clasificó como pequeños, medianos y grandes de acuerdo con un análisis de clúster de dos pasos. Se utilizó estadística descriptiva y la prueba de chi-cuadrado con un nivel de significancia del 5%. RESULTADOS: de las 362 instituciones incluidas, 308 (85,1%) se adhirieron a 14 o más recomendaciones. En cuanto a su tamaño, la adhesión al cribado de síntomas de COVID-19 de los visitantes (p=0,037) y al aislamiento de los pacientes hasta que tengan dos pruebas de laboratorio negativas (p=0,032) fue menor en los establecimientos más grandes en comparación con los establecimientos medianos y pequeños. CONCLUSIÓN: la adhesión a las medidas de mitigación de la COVID-19 en las unidades brasileñas fue considerada excelente para la mayoría de las recomendaciones, independientemente del tamaño de las unidades.

OBJETIVO: avaliar a adesão das instituições de longa permanência brasileiras às orientações de Prevenção e Controle de Infecções da Organização Mundial da Saúde, observando a associação entre seu porte e a adesão a essas recomendações. MÉTODO: estudo transversal realizado com gestores de estabelecimentos. Os autores desenvolveram um questionário de 20 itens, com base nessas orientações, e um escore global de adesão, com base na adesão a essas recomendações. A adesão foi classificada como (1) excelente para aquelas que atenderam ≥14 de 20 recomendações, (2) bom para 10 a 13 itens e (3) baixo para aquelas com menos de dez itens. O tamanho das instalações foi classificado como pequeno, médio e grande, de acordo com uma análise de cluster em duas etapas. Estatística descritiva e teste de qui-quadrado foram utilizados com nível de significância de 5%. RESULTADOS: das 362 instituições incluídas, 308 (85,1%) aderiram a 14 ou mais recomendações. Em relação ao seu tamanho, a adesão à triagem de sintomas de COVID-19 dos visitantes (p=0,037) e ao isolamento de pacientes até que tenham dois exames laboratoriais negativos (p=0,032) foi menor em estabelecimentos maiores, em comparação com estabelecimentos de médio e pequeno porte. CONCLUSÃO: a adesão às medidas de mitigação da COVID-19 nas unidades brasileiras foi considerada excelente para a maioria das recomendações, independentemente do porte das unidades.
Impact of long-term care facilities' size on adherence to COVID-19' infection prevention guidance